Resilience of the samin community in the face of climate change in Java Island, Indonesia - Wibowo Agung; Wardojo Waskito Widi; Rahmanto Andre Noevi; Candrakirana Rosita (BIO Web of Conferences)
The Samin Community has a rich traditional knowledge system which plays an important role in maintaining social and ecological resilience. Climate change has a significant impact on indigenous communities worldwide. This research aims to understand how the Samin community maintains and strengthens resilience amidst extreme climate change, and how local wisdom can be integrated with modern knowledge and technology to achieve long-term sustainability. The research uses a qualitative method with a case study strategy and ethnography, to describe and explore the resilience of the Samin community. The target of a qualitative approach is a comprehensive description of social life. The analysis combines the stages of data reduction, data presentation, and drawing of a conclusion in a repetitive, cyclic way. The research results show that a holistic approach combining local wisdom, modern technology, and policy is the key to sustainability of the Samin community in the face of climate change